Debt and Transfer Pricing: Implications on Business Tax Policy - Nicola Comincioli; Paolo M. Panteghini; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2020)
In this article we introduce model to describe the behavior of a multinational company (MNC) that operates transfer pricing and debt shifting, with the purpose of incrementing its value, intended as the sum of equity and debt. We compute, in a stochastic environment and under default risk, the optimal shares of profit and debt to be shifted and show how they are affected by exogenous features of the market. In addition, by means of a numerical analysis, we simulate and quantify the benefit arising from the exploitation of tax avoidance practices and study the corresponding impact on MNC's fundamental indicators. A wide sensitivity analysis on model's parameters is also provided.
Keywords: H25; G33; G38; 330; Capital Structure; Default Risk; Business Taxation and Welfare